2014
DOI: 10.1097/opx.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Refractive Change and Ocular Parameter Changes after Cycloplegia

Abstract: Spherical equivalent of refractive error, AL, and ACD all positively shifted after cycloplegia with tropicamide. Corneal curvature became flattened after cycloplegia with tropicamide, but the corneal astigmatism did not change significantly. Refractive changes did not correlate with changes in AL, ACD, or CC after cycloplegia with tropicamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 28 publications
7
48
1
Order By: Relevance
“…Previous studies that examined the effects of accommodation on the refractivity of the cornea have had varying results. While Cheng et al 7 detected corneal flattening after instilling 0.04% tropicamide, Yasuda et al 15 reported an increase in corneal power after inducing ciliary muscle contraction with 4% pilocarpine. It is believed that ciliary muscle contraction causes corneal steepening by acting on the peripheral cornea via the scleral spur, whereas after cycloplegia this effect is eliminated and the cornea flattens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies that examined the effects of accommodation on the refractivity of the cornea have had varying results. While Cheng et al 7 detected corneal flattening after instilling 0.04% tropicamide, Yasuda et al 15 reported an increase in corneal power after inducing ciliary muscle contraction with 4% pilocarpine. It is believed that ciliary muscle contraction causes corneal steepening by acting on the peripheral cornea via the scleral spur, whereas after cycloplegia this effect is eliminated and the cornea flattens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to refractive changes, preventing accommodation also leads to changes in anterior segment structures. 6,7,8,9,10 Keratoconus typically begins in childhood, progresses into the 40s, and then halts progression. 1 Accommodation is also at full capacity in this age group, and the effect of accommodation should not be overlooked when evaluating visual complaints.…”
Section: The Effect Of Topical Cyclopentolate On Anterior Segment Parmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found corneal steepening with ciliary contraction and corneal flattening with cycloplegia [11, 12] while others have not found such an effect [13, 14]. Studies on myopic eyes have revealed corneal flattening with cycloplegia [12, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…A blocked accommodation and the resultant decrease in lens power have historically been thought to be the reason for the postcycloplegia refractive changes. However, it is possible that the corneal power, ACD, and AL changes that are also present in this state influence the refractive state following cycloplegia [12]. This can be explained as the ACD changes are likely due to lens changes and the changes in corneal power can be calculated from the changes in K readings before and after cycloplegia.…”
Section: Discussionmentioning
confidence: 99%